Insights into Unloading Relaxation Mechanism of Columnar Jointed Basalt at the Baihetan Left Dam Foundation - Jian-cong Zhang; Shu-feng Pei; Xiao Xu; Hao-ran Li (Advances in Materials Science and Engineering, 2021)
Columnar jointed basalt (CJB), characterized by unique geometric and geological properties, poses a great challenge for geotechnical designs due to its unloading relaxation and damage during excavation. In this paper, the geometrical structure and field failures of the CJB exposed on Baihetan left dam foundation were briefly presented. A systematic field test was conducted to study the excavation damage zone of the CJB on the dam foundation using ultrasonic P wave measurements. The excavation damage zone of the CJB not only showed time-dependent damage in depth but also showed spatially inhomogeneous distribution in depth. Corresponding three-dimensional numerical analysis was also carried out to analyze the unloading relaxation mechanism of CJB. The unloading relaxation of CJB on dam foundation was mainly caused by the joint opening under tension stress during excavation. The difference of excavation damage zone of the CJB located in different test zones was also discussed in this article.